ADOLESCENTS EXPERIENCING PARENTAL CANCER: A QUALITATIVE STUDY - Ana Filipa Domingues Sousa; Diana Gabriela Simões Marques Santos; Maria Margarida da Silva Reis dos Santos Ferreira; Maria de Lurdes Lopes de Freitas Lomba (Universidade Federal do Paraná, 2024)
Objective: to analyze the needs of adolescents experiencing parental cancer. Method: an exploratory and descriptive qualitative study. Data collection was carried out through semi-structured interviews in 2021. The convenience sample was composed of adolescents aged 14-19, with parents with oncological disease in the treatment phase, followed in a Portuguese oncology hospital. Data processing was carried out using content analysis. Results: from the analysis of the 13 interviews, five domains emerged: Coping with the disease; Knowledge about the disease; Previous experiences with the oncological disease; Experiencing parental cancer; and Somatic changes. The results show that adolescents experiencing parental cancer have emotional, educational and psychosocial needs. Conclusion: this study allowed us to understand adolescents' needs, understanding the difficulties experienced and the challenges that the experience entails. The results will support the design of a nursing intervention program for the dyad experiencing parental cancer.